Peran Pemerintah Kabupaten Banjarnegara dalam Pemberian Upah Minimum: Kesesuaian dengan Surat Keputusan Gubernur Jawa Tengan Nomor 561/57 Tahun 2023 - Aysah, Ayu Siti Nurul (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to examine the role of the Government, especially in this case the Manpower Office, which has an active role in supervising workers in getting salaries in accordance with government regulations, and legal efforts against companies that have not set minimum wage standards, minimum wage is one of the important instruments in protecting workers' welfare and ensuring fairness in work compensation. This study uses a qualitative approach with the Empirical Juridical method, which uses field data collection as the main data such as through interviews, observations, and analysis of policy documents and applicable regulations. This research is expected to contribute to improving the welfare of the people in Banjarnegara Regency by increasing the minimum wage and ensuring the welfare of workers in the region. The results of the research obtained by the author that the role of the Banjarnegara PMPTSP Manpower Office has a monitoring and socialization role as well as a meeting to determine the district minimum wage every year, and has legal efforts in the process of complaints of UMK violations with the availability of the Complaints Agency Commission and the First Expert Mediator to resolve conflicts of UMK violations by the reported workers against companies in Banjarnegara.